PENGELOLAAN SDM DESA WISATA COLOL : KUNCI PENGEMBANGAN DESA WISATA BERKELANJUTAN - Hersanius Kurnia Peong; Laurensius Sandrio; Yosef Kurniawan Ukar (Jurnal Penelitian Terapan Mahasiswa, 2023)
Abstract The complexity of world business with a high level of competition requires creativity and innovation from all Parties. One of the important sector that is developing in response to the issue of competition is tourism sector through tourism villages. The existence of a Tourism Village can boost the national and local economy through increasing the welfare of the community as the main actor in a Tourism Village. This research is motivated by the urgency of managing human resources as an important factor in improving the quality of tourism villages. This practice has become an important discourse so that researchers are motivated to explore one of the Tourism Villages in East Manggarai, namely Colol Village with its unique tourist destinations. This research uses a qualitative descriptive approach with a case study type to determine the extent to which the implemented HR management practices affect the sustainability of this Tourism Village. Researchers collected data by conducting observations and interviews with several Colol Tourism Village stakeholders. The results of the study said that there were several things carried out by the managers even though there were still some limitations in several aspects. Some of these things are HR planning, institutional strengthening, community mobilization, and controlling tourism actors with FGD and Monev. Some of these practices are carried out to maintain this Tourism Village so that it continues to exist in the future.